Historical Property Rights, Sociality, and the Emergence of Impersonal Exchange in Long-Distance Trade - Kimbrough, Erik O; Smith, Vernon L; Wilson, Bart J (American Economic Review, 2008)
This laboratory experiment explores the extent to which impersonal exchange emerges from personal exchange with opportunities for long-distance trade. We design a three-commodity production and exchange economy in which agents in three geographically separated villages must develop multilateral exchange networks to import a good only available abroad. For treatments, we induce two distinct institutional histories to investigate how past experience with property rights affects the evolution of specialization and exchange. We find that a history of unenforced property rights hinders our subjects' ability to develop the requisite personal social arrangements to support specialization and effectively exploit impersonal long-distance trade. (JEL C90, D23, D51, P14)